Pengaruh Pajak Hotel, Pajak Restoran, Pajak Hiburan, dan Pajak Reklame terhadap Pendapatan Asli Daerah Kota Bogor - Azis, Nia Fakhriyah; Susanto, Heri; Yulia, Iis Anisa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the influence of Hotel Tax, Restaurant Tax, Entertainment Tax, and Advertisement Tax on Regional Original Income in the City of Bogor. The sample used in this research consists of data from the last 10 years, from 2014 to 2023. Data was collected using a purposive sampling method, and hypothesis testing was conducted using Multiple Linear Regression Analysis. The results of this research show that Hotel Tax has a significant effect on Regional Original Income, Restaurant Tax has a significant effect on Regional Original Income, Entertainment Tax has a significant effect on Regional Original Income, and Advertisement Tax has a significant effect on Regional Original Income. Furthermore, Hotel Tax, Restaurant Tax, Entertainment Tax, and Advertisement Tax have a simultaneous effect on Regional Original Income